Konflik Sosial dalam Kumpulan Cerpen “Kembali ke Pangkal Jalan” Karya Yusrizal K.W. - Harahap, Holijah; Amrizal, Amrizal; Hiasa, Fina (Jurnal Korpus, 2025)
The purpose of this study is to find out what forms of social classes occur from the collection of short stories through behavior, attitudes of characters in the collection of short stories "Back to the Base of the Road" by Yusrizal K.W. And find out the factors causing social conflict in the collection of short stories "Back to the Base of the Road" by Yusrizal K.W. Using Karl Marx's theory of social conflict. This research uses a qualitative approach description method. The data from the study is data in the form of words, phrases, expressions, and sentences contained in the collection of short stories "Kembali ke Pangkal Jalan" by Yusrizal K.W. published in October 2004 by Kompas, Jakarta, which are 14 titles of short stories selected by Yusrizal KW written from the 2000s to 2004, and only 9 titles want to be analyzed because of social themes. The results of this study are the factors causing social conflict in the collection of short stories "Kembali Pangkal Jalan" by Yusrizal K.W. Social conflict in the collection of short stories "Kembali Pangkal Jalan Karya Yusrizal K.W" bourgeoisie or ruling class and proletariat or class that has no power. The ruling upper class is the people who own the means of production such as merchant societies, subdistrict mothers, rich people, leaders, while the lower class (proletariat) who have the power and do not have the means of production like thug gangs. lay people, poor families.